Some Aspects of the History and Civilization of the Lycians and their Antecedents (with special reference to the Lycian Sepulchral Inscriptions) - Bryce, T. R.
PhD Diss.; laut Kadmos 17 (1978) 175, cf. Sprache 25 (1979) 206.